Pengaruh Kemitraan Koperasi Unit Desa dengan Peternak Sapi Perah terhadap Kesejahteraan Anggota Kemitraan Desa Nglurup Kecamatan Sendang Kabupaten Tulungagung - Toifur Ahmad Balya; Nur Lailiyah (Universitas Nusantara PGRI Kediri, 2025)
Starting from the urgency of the role of Village Unit Cooperatives (KUD) in improving the quality of life in rural communities, this study aims to examine the implementation of partnership patterns, the supporting and inhibiting factors, as well as their impact on members’ welfare. The research focuses on the partnership between KUD and dairy farmers in Nglurup Village, Sendang District, Tulungagung Regency. A quantitative approach was employed through a survey of 211 partnership members. Data were collected using a closed-ended Likert-scale questionnaire and structured observations with specific guidelines. The validity and reliability of the instruments were tested using Pearson correlation analysis and Cronbach’s Alpha. Data analysis was conducted using simple linear regression to determine the effect of the partnership variable (X) on welfare (Y). The results indicate that the partnership between KUD and dairy farmers has a significant impact on members’ welfare. The coefficient of determination shows that the partnership contributes positively in explaining variations in welfare levels. In conclusion, strengthening the partnership model between KUD and dairy farmers needs to be continuously enhanced as a strategy to support rural economic development based on local wisdom. These findings are expected to serve as a reference for formulating economic empowerment policies in rural areas.